Magnetic nanomaterials in analytical chemistry - Ahmadi, Mazaher; Afkhami, Abbas; Madrakian, Tayyebeh (Elsevier, 2021)
Magnetic Nanomaterials in Analytical Chemistry provides the first comprehensive review of magnetic nanomaterials in a variety of analytical chemistry applications, including basic information necessary for students and those new to the topic to utilize them. In addition to analytical chemists, those in various other disciplines where these materials have great potential--e.g., organic chemistry, catalysis, sensors--will also find this a valuable resource. Magnetic nanomaterials that can be controlled using external magnetic fields have opened new doors for the development of new sample preparation methods and novel magnetic sorbents for forensic chemistry, environmental monitoring, magnetic digital microfluidics, bioanalysis, and food analysis. In addition, they are seeing wide application as sensing materials in the development of giant magnetoresistive sensors, biosensors, electrochemical sensors, surface-enhanced Raman spectroscopy sensors, resonance light scattering sensors, and colorimetric sensors. Includes fundamental information on magnetic nanomaterials, including their classification, synthesis, functionalization, and characterization methods, separation and isolation techniques, toxicity, fate, and safe disposal Each chapter describes a specific application Utilizes figures, schemes, and images for better understanding of the principles of the method Presents information on advanced methods, such as giant magnetoresistive and magnetic digital microfluidics